Trial of Fingolimod versus Interferon Beta-1a in Pediatric Multiple Sclerosis. - Chitnis, Tanuja; Arnold, Douglas L.; Banwell, Brenda; Brueck, Wolfgang; Ghezzi, Angelo; Giovannoni, Gavin; Greenberg, Benjamin; Krupp, Lauren; Rostasy, Kevin; Tardieu, Marc; Waubant, Emmanuelle; Wolinsky, Jerry S.; et al. (New England Journal of Medicine, 2018)
BACKGROUND: Treatment of patients younger than 18 years of age with multiple sclerosis has not been adequately examined in randomized trials. We compared fingolimod with interferon beta-1a in this population. METHODS: In this phase 3 trial, we randomly assigned patients 10 to 17 years of age with relapsing multiple sclerosis in a 1:1 ratio to receive oral fingolimod at a dose of 0.5 mg per day (0.25 mg per day for patients with a body weight of ≤40 kg) or intramuscular interferon beta-1a at a dose of 30 μg per week for up to 2 years. The primary end point was the annualized relapse rate. RESULTS: Of a total of 215 patients, 107 were assigned to fingolimod and 108 to interferon beta-1a. The mean age of the patients was 15.3 years. Among all patients, there was a mean of 2.4 relapses during the preceding 2 years. The adjusted annualized relapse rate was 0.12 with fingolimod and 0.67 with interferon beta-1a (absolute difference, 0.55 relapses; relative difference, 82%; P<0.001). The key secondary end point of the annualized rate of new or newly enlarged lesions on T2-weighted magnetic resonance imaging (MRI) was 4.39 with fingolimod and 9.27 with interferon beta-1a (absolute difference, 4.88 lesions; relative difference, 53%; P<0.001). Adverse events, excluding relapses of multiple sclerosis, occurred in 88.8% of patients who received fingolimod and 95.3% of those who received interferon beta-1a. Serious adverse events occurred in 18 patients (16.8%) in the fingolimod group and included seizures (in 4 patients), infection (in 4 patients), and leukopenia (in 2 patients). Serious adverse events occurred in 7 patients (6.5%) in the interferon beta-1a group and included infection (in 2 patients) and supraventricular tachycardia (in 1 patient). CONCLUSIONS: Among pediatric patients with relapsing multiple sclerosis, fingolimod was associated with a lower rate of relapse and less accumulation of lesions on MRI over a 2-year period than interferon beta-1a but was associated with a higher rate of serious adverse events. Longer studies are required to determine the durability and safety of fingolimod in pediatric multiple sclerosis. (Funded by Novartis Pharma; PARADIGMS ClinicalTrials.gov number, NCT01892722 .).
EVALuna2:35720